PENGARUH E-SERVICE QUALITY DAN E-RECOVERY TERHADAP REPURCHASE INTENTION PENGGUNA TOKOPEDIA, DENGAN E-LOYALTY SEBAGAI VARIABEL MEDIASI - imany, wulan sukma; Tiarawati, Monika (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Tokopedia is one of the online shopping platforms created by Indonesia. Referring to data collected by iPrice, in the second quarter (Q2) of 2021 Tokopedia had the most monthly web visitors in Indonesia. Total visitors to Tokopedia averaged 147,790,000 per month. However, in pikiran rakyat.com there are many letters from readers regarding complaints about using Tokopedia. This study aims to determine the effect of E-Service Quality and E-Recovery on Repurchase Intention of Tokopedia Users, with Customer Loyalty as a Mediating Variable. The sample in this study were 120 people who complained about the reliability of the services provided by Tokopedia and received a response from Tokopedia. The analysis technique used in this research is the Structural Equation Model (SEM) using the Partial Least Square (PLS) analysis method supported by the Smart-PLS 3.0 application.The results showed that (1) e-service quality has a positive effect on Tokopedia user e-loyalty; (2) e-service quality has a positive effect on repurchase intention; (3) e-recovery has a positive effect on e-loyalty; (4) e-recovery has no effect on repurchase intention; (5) e-loyalty mediates the positive effect of e-service quality on repurchase intention; and (7) e-loyalty mediates the positive effect of e-recovery on repurchase intention.